Faktor-Faktor Yang Mempengaruhi Tingkat Kepercayaan Masyarakat Terhadap Lembaga Keuangan Syariah: Studi Kasus Masyarakat Kabupaten Labuhan Batu Selatan - Widia Wulandari; Dahrani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of Information Technology should make companies grow more rapidly, including Sharia Financial Institutions, both in terms of receiving and distributing funds, but in reality we can see that Islamic financial institutions still tend to be less developed than conventional financial institutions, this is caused by many factors, and Therefore, the aim of this research is to find out whether human resources in Islamic financial institutions, namely employees and the products offered, can influence the level of public trust in Islamic financial institutions, either partially or simultaneously. This type of research is quantitative using a questionnaire as a data collection method which is then tested using multiple linear regression analysis. The research results show that human resources or employees from Islamic Financial Institutions have a positive influence with a significant value of 0.000, while the products offered influence Islamic financial institutions with a significant value of 0.000, while simultaneously the two independent variables have a positive influence with a significance value of 0.000.